Miłosny savoir-vivre w świetle listowników dla zakochanych z końca XIX i początkowych dekad XX wieku = Amorous savoir-vivre in the light of the model love letters released at the end of 19th and in the first decades of 20th century - Jazownik, Leszek (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The end of the 19th century saw the rise in the popularity of model letters for lovers, containing their exemplars which purpose was to ease maintaining romantic correspondence. Despite the fact that such letters are fictional in nature, they are valuable documents representing the mores of the epoch in which they were created. They constituted a kind of amorous savoir-vivre handbook.
Keywords: sztuka epistolarna; listowniki; wzory korespondencji; miłosny savoir-vivre; kultura obyczajowa XIX i XX wieku; epistolary art; model letters; amorous savoir-vivre; mores of the 19 and 20th centuries